Covered Interest Parity and XVAs - Pavlou, Danae (Department of Finance and Tax, 2025)
Covered interest parity relies on a traditional no-arbitrage argument and states that the difference in interest rates between two currencies should be linked to the spot and forward exchange rates. One would expect an arbitrage opportunity to be traded away, however, the covered interest parity relationship has been shown to break down with the arbitrage opportunity persisting. This dissertation seeks to show that valuation adjustments can be considered one of the reasons why covered interest arbitrage persists. A classic covered interest parity trade is considered, where we borrow directly from the South African market and simultaneously synthetically lend rand, which involves entering a foreign exchange contract to fix the exchange rate. From this setup, we look to derive, from first principles, the net value of the strategy, highlighting the funding valuation adjustment. Further, the default of both parties within the strategy is considered, which allows us to consider the credit valuation adjustment and the debt valuation adjustment.